Correlação entre a infecção genital pelo vírus do papiloma humano, a resposta imune e os achados colpocitológicos em mulheres grávidas e não grávidas - Lima, érika Galvão de (2012)
The genital HPV infection is very common between men and women worldwide, affecting particularly young women, constituting a serious public health problem in less developed regions, favored by the poor living conditions of population. The cytology and colposcopy have notorious importance in the diagnosis of precursor lesions of cervical cancer and therefore its prevention. However, even with such diagnostic tools, the number of women who develop cervical cancer is still high. This study aims to assess the prevalence of genital tract infection by HPV in pregnant and nonpregnant women, evaluating the profile of the immune response presented by the women of these two groups in order to establish correlations among profile of immune response, presence of virus and occurrence of lesions of the uterine cervix. We analyzed specimens obtained from the cervix of 221 patients, 91 pregnant and 130 non-pregnant, aged 14-72 years. The women were subjected to colposcopic and cytologic evaluation detect possible changes in the cervix and then samples were collected in order to perform HPV detection by PCR and real-time PCR for detection of mRNA of pro-inflammatory and anti-inflammatory cytokines. In the present study, the overall prevalence of HPV genital infection was 28.1%; of which 31.9% were pregnant patients and 25.4% in non-pregnant women. Young women under 30 years and those with low educational level education showed a higher risk of HPV infection. Colposcopy showed better correlation with detection of HPV DNA by PCR, when compared to cytology. Generally, HPV infected patients, pregnant or not, exhibited reduced mRNA expression of both pro-inflammatory (IFN-γ, TNF-α) and anti-inflammatory (IL -10) cytokines, when compared to patients not infected by HPV. Nonpregnant patients infected presented increase mRNA expression of IL-17 in patients without injury, whereas those with lesion showed higher mRNA expression of TGF-β. Pregnant women without injury infected exhibited increased mRNA expression of TGF-β. There was no difference in HPV prevalence between pregnant and nonpregnant women. There was a reduction of pro-inflammatory cytokines, except IL-17, in all women infected by HPV. Moreover, we observed an increase of TGF-β in HPV-infected women who are pregnant or not. The results suggest that, in women in this study, HPV infection promoted changes in the profile of cytokines necessary for activation of effective immune response, possibly favoring viral persistence